2019
DOI: 10.1039/c8ee02601g
|View full text |Cite
|
Sign up to set email alerts
|

Bisalt ether electrolytes: a pathway towards lithium metal batteries with Ni-rich cathodes

Abstract: Breakthroughs in performance of Li/Cu with Ni-rich cathodes can be achieved via manipulation of anion interfacial chemistry, as uncovered by experiment/modeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
288
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 350 publications
(312 citation statements)
references
References 100 publications
3
288
0
7
Order By: Relevance
“…A similar result is also found from the peak at 533.8 eV identified with the presence of ROCOOLi in the O 1s spectrum of both the samples. In the F1s spectrum, the peaks at around 687.7, 686.8, and 684.8 eV are attributed to PVDF, Li x PO y F z , LiF, the larger percentage of Li x PO y F z and LiF resulting from side reactions further prove the surface pillar effect . The EIS measurement is also employed to investigate the change of the surface film of the electrodes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar result is also found from the peak at 533.8 eV identified with the presence of ROCOOLi in the O 1s spectrum of both the samples. In the F1s spectrum, the peaks at around 687.7, 686.8, and 684.8 eV are attributed to PVDF, Li x PO y F z , LiF, the larger percentage of Li x PO y F z and LiF resulting from side reactions further prove the surface pillar effect . The EIS measurement is also employed to investigate the change of the surface film of the electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…In the F1s spectrum, the peaks at around 687.7, 686.8, and 684.8 eV are attributed to PVDF, Li x PO y F z , LiF, the larger percentage of Li x PO y F z and LiF resulting from side reactions further prove the surface pillar effect. [46] The EIS measurement is also employed to investigate the change of the surface film of the electrodes. As shown in Figure S9, the Nyquist plots of both samples at 4.3 V after a cycle and 200 cycles are composed of an inclined line and two semicircles which are related to the surface film impedance R sf and charge transfer impedance R ct .…”
Section: Full Papermentioning
confidence: 99%
“…Very recently, Dahn and co‐workers reported that anode‐free lithium‐metal pouch cells with a LiDFOB/LiBF 4 (FEC/DEC) blended‐salt electrolyte had 80 % capacity remaining after 90 charge–discharge cycles, which is the longest life demonstrated to date for cells with zero excess lithium . Therefore, a blended‐salt electrolyte is a very good choice to significantly improve the performance of the extremely challenging anode‐free LMBs …”
Section: Discussionmentioning
confidence: 99%
“…[89] The additional LiFSI co-salt significantly enhanced the lithium-ion-transfer process and enabled homogenous Li deposition (Figure 4 d- More recently, a highly concentrated blended-salt electrolyte (4.6 m LiFSI + 2.3 m LiTFSI in DME) was formulated by Xu and co-workers to endow plated Li metal with a denser, more conformal morphology ( Figure 5 a-f), and this electrolyte also exhibited excellent oxidative stability ( Figure 5 g). [45] Furthermore, far more challenging 4.4 V LMBs of NCM622/ Li ( Figure 5 h) and NCM622/Cu (Figure 5 i) based on a cathode with a high Ni content, LiNi 0.6 Mn 0.2 Co 0.2 O 2 (NCM622), showed unprecedented cyclability ( Figure 5 g-i), breaking the long-standing voltage limitation for ether-based electrolytes. Through a combination of electrochemical, spectroscopic (cryogenic transmission electron microscopy (cryo-TEM), and X-ray photoelectron spectroscopy (XPS)), and computational approaches (Figure 5 j,k), a thorough mechanistic understanding of how the two anions FSI and TSFI behaved at electrode-electrolyte interfaces of the anode and the cathode was attained.…”
Section: Lithium-imide-based Blended-salt Electrolytesmentioning
confidence: 99%
“…In recent years, nickel‐rich Li[Ni x Co y Mn 1− x − y ]O 2 (NCM) layered cathode materials ( x ≥ 0.6) are of special interest for lithium‐ion batteries (LIBs). [ 1–4 ] This is because they can deliver high specific capacity (>180 mAh g −1 ) without the need to increase the charging potential to levels that go beyond the stable operating voltage window. As a cathode counterpart, graphite has been the most commercially successful anode material for LIBs due to its low material cost and reduction potential (≈0.05 V vs Li/Li + ).…”
Section: Introductionmentioning
confidence: 99%